Analisis Tingkat Familiaritas Siswa Terhadap Istilah Sains dan Biologi - Sifa Lasira Aprilia; Ogi Danika Pranata; Toni Haryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine students' familiarity with science and biology terms. This research uses descriptive and comparative quantitative methods which were carried out at SMA Negeri 6 Kerinci. The data is processed and analyzed descriptively to obtain a general picture of students' familiarity with scientific terms. Then use the independent samples t-test to compare students' familiarity with terms at different grade levels and the paired sample t-test to compare the level of students' familiarity with general science and biology terms. The results showed that class XI MIPA students (2.58) were more familiar with general science and biology terms than class XII MIPA students (2.06). Significant differences were also found between students' familiarity with general science and biology terms. Students at SMA Negeri 6 Kerinci tend to be more familiar with biology terms (2.44) compared to general science terms (2.05). In conclusion, a) the level of familiarity was found not to be in line with grade level; b) there is a high and significant correlation between students' familiarity with general science and biology terms; c) there is a significant difference between students' familiarity with general science terms and biology. Keywords: Biology, Familiarity, Scientific Terms, Science, Students